Design of Modified HRRN Scheduling Algorithm for priority systems Using Hybrid Priority scheme - P. Surendra Varma (Journal of Telematics and Informatics, 2013)
The basic aim of this paper is to design a scheduling algorithm which is suitable for priority systems and it should not suffer with starvation or indefinite postponement. Highest Response Ratio Next (HRRN) scheduling is a non-preemptive discipline, in which the priority of each job is dependent on its estimated run time, and also the amount of time it has spent waiting. Jobs gain higher priority the longer they wait, which prevents indefinite postponement (process starvation). In fact, the jobs that have spent a long time waiting compete against those estimated to have short run times. HRRN prevents indefinite postponements but does not suitable for priority systems. So, modifying HRRN in such a way that it will be suitable for priority based systems.